Reasons for Parents Choosing Private Schools - Orhan, Mustafa; Demirkol, Murat (Yildiz Technical University, 2025)
In contemporary society, characterised by an escalating demand for private educational institutions, it is imperative to discern the underlying factors that motivate parents to opt for these schools. This understanding is crucial for a comprehensive evaluation of educational policies and the expectations of families. The objective of this study is to ascertain the factors that motivate parents to enrol their children in private schools. The study was designed using a phenomenological approach, incorporating qualitative research methods. The study group for the research project consists of 32 parents of students enrolled in primary, secondary and high schools in the central districts of Aziziye, Palandöken and Yakutiye in Erzurum province. The selection of participants was conducted using the maximum diversity sampling method. The research data were obtained through the utilisation of a semi-structured interview form. The data was analysed using a content analysis method. The study concluded that the predominant rationale for parents’ inclination towards private schools was the perceived quality of education. It is evident that parents of pupils at private schools have expectations of a high standard of education. The private school has endeavoured to meet these expectations by communicating with parents. It is evident from the research that the quality of education is a primary concern for parents when selecting private schools. This indicates that factors influencing educational quality should be given due consideration. Nevertheless, it can be argued that the inferences made for private schools can also be made for public schools. However, it can be said that the inferences made for private schools can also be made for public schools.

Özel okullara olan talebin giderek arttığı günümüzde, velilerin bu okulları tercih etme nedenlerini anlamak, eğitim politikalarının ve ailelerin beklentilerinin daha iyi kavranması açısından büyük önem taşımaktadır. Bu kapsamda çalışmanın amacı, velilerin özel okul tercih nedenlerini belirlemektir. Çalışma nitel araştırma yöntemlerinden olgu bilim deseninde tasarlanmıştır. Araştırmanın çalışma grubunu Erzurum ili Aziziye, Palandöken ve Yakutiye merkez ilçelerindeki ilkokul, ortaokul ve liselerde çocuğu öğrenim gören ve maksimum çeşitlilik örnekleme yöntemiyle seçilen 32 öğrenci velisi oluşturmaktadır. Araştırma verileri, yarı yapılandırılmış görüşme formu ile elde edilmiştir. Verilerin analizinde içerik analizi yöntemi kullanılmıştır. Araştırmada velilerin özel okul tercih nedenlerinde en fazla, eğitim kalitesi görüşünün ifade edildiği belirlenmiştir. Velilerin özel okuldan beklentilerinde en fazla kaliteli eğitim ifadesi; özel okulun, veli beklentilerini karşılamak için yaptıklarında ise en fazla iletişim ifadesi ön plana çıkmıştır. Araştırmada velilerin özel okul tercihlerinde ve özel okul beklentilerinde eğitimin kalitesi görüşünün ön planda olması; eğitimin kalitesine etki edebilecek unsurların dikkate alınması gerektiği sonucunu ortaya çıkardığını söylemek mümkündür. Bununla birlikte özel okullara yönelik yapılan çıkarımların resmi okullar için de yapılabileceği söylenebilir.
Velilerin Özel Okul Tercih Nedenleri
Keywords: Education Management; Eğitim Yönetimi